The Transition of Dramaturgy During Pandemic: From Staging to Streaming - Dede Pramayoza; Pandu Birowo (Journal of Urban Society's Arts, 2022)
This study discusses the transition of performances dramaturgy during the Covid-19 pandemic from analog to digital formats, from live performances commonly called staging to mediated performances which can be called performance streaming. The aim of study is to understand the application of ‘dramaturgical tactics’; and the reasons. Applying the dramaturgical analysis method investigation is directed at the transformation process from the basic concept of the performance to the practice of its presentation. The research departs from the premise that a dramaturgical process, namely the pre-production, production, and presentation of performance is permanently connected by a dramaturgical awareness. The analysis was carried out: (1) the idea of streaming; (2) performance technique; and (3) the form of performance streaming. Research shows that the critical changes in dramaturgy during the pandemic were triggered by the necessity to shift the mode of performance from staging to streaming, resulting in three dramaturgical awareness about transition, namely: (1) medium: from analog to digital performance; (2) creativity: from performer to content creator; and (3) the spectatorship: from spectator to voyeur. Perubahan Dramaturgi di Masa Pandemi: Dari Pementasan ke Siaran. Artikel ini membahas perihal transisi dramaturgi pertunjukan di masa pandemi Covid-19 dari format analog ke format digital, dari moda pertunjukan langsung yang lazim dinamakan pementasan ke pertunjukan termediasi yang dapat dinamakan siaran pertunjukan. Tujuannya untuk memahami bentuk penerapan ‘siasat dramaturgi’ serta alasan di baliknya. Mengunakan metode analisis dramaturgis, berupa investigasi atas proses transformasi dari konsep dasar pertunjukan menuju praktik presentasinya, penelitian berangkat dengan premis bahwa suatu proses  dramaturgi, yakni tahap pra-produksi, produksi, dan presentasi pertunjukan selalu terhubung oleh satu kesadaran dramaturgis. Analisis dilakukan terhadap: (1) gagasan siaran pertunjukan; (2) teknik siaran pertunjukan; dan (3) bentuk siaran pertunjukan. Penelitian menunjukkan bahwa, perubahan penting dramaturgi di masa pandemi dipicu oleh suatu keharusan untuk memindahkan moda pertunjukan dari pementasan ke siaran, menghasilkan tiga kesadaran dramaturgis tentang peralihan, yakni: (1) medium: dari pementasan analog ke siaran digital; (2) kreativitas: dari penampil menjadi pembuat konten; dan (3) kepenontonan: dari spektator menjadi voyeur.